2021
DOI: 10.5267/j.msl.2021.2.009
|View full text |Cite
|
Sign up to set email alerts
|

Country governance, tourism and environment quality: An emerging economy perspective

Abstract: The objective of the study has two folds: first, the study analyzes the role of country governance in tourism. Second, the study investigates the impact of tourism on the environmental quality. For this purpose, the data from 1997 to 2018 are collected from the World Bank and Global Economy. Augmented Dickey Fuller (ADF) test and ordinary least square regression models are used to analyze the impact. The study finds positive impact of rule of law, control of corruption, political stability and government effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results indicated that political stability played a significant role in influencing tourist demand in the long term, emphasizing a clear preference for destinations characterized by political stability. Akram et al (2021) assessed the impact of good land management on tourism and its effect on the environment. They found that corruption control, political stability, absence of violence, and government effectiveness positively influenced tourism, advocating for improved institutional involvement in tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that political stability played a significant role in influencing tourist demand in the long term, emphasizing a clear preference for destinations characterized by political stability. Akram et al (2021) assessed the impact of good land management on tourism and its effect on the environment. They found that corruption control, political stability, absence of violence, and government effectiveness positively influenced tourism, advocating for improved institutional involvement in tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The significance of effective governance practices in influencing energy consumption has been mentioned in the literature (Akram, Sultana, Sultana, Majeed, & Saeed, 2021;Haseeb, Hassan, Azam, & Suryanto, 2018). The linkage between governance-related factors and energy consumption patterns as well as CO2 emissions have been examined by Friedman and Gürce (2020); Nguyen (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…FDI-related factors that influence energy consumption patterns and CO2 emissions in a subset of Muslim countries are examined by Muhammad, Khan, Razzaq, andKarim (2021) andFaqeer, Khan, Naveed, andRehmat (2021). Akram et al (2021); Islam, Mindia, Farzana, and Qamruzzaman (2023); Yudina, Vandina, Bogoviz, and Lobova (2017) indicated that economic development and the environment were interconnected. The effectiveness of governments, encompassing governance quality, democratization, adherence to environmental regulations, corruption control, efficient tax systems, and political stability, influences the propensity of economic agents to comply with such regulations and carry out activities in a manner that mitigates environmental damage (Azam et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modern tourism studies focus largely on sociological perspectives on tourist activities [1][2][3][4][5] and environmental aspects of tourism development [6][7][8][9][10]. In other words, tourism is considered as a social phenomenon with an evident ecological impact.…”
Section: Introductionmentioning
confidence: 99%